Review of Reis, M. C. G. Cartas & Máximas Principais, “Como um deus entre os homens”(2020) - Vieira, Celso (Revista Archai, 2022)
Review of Reis, M. C. G. Cartas & Máximas Principais, “Como um deus entre os homens”(2020)